CD28 days later: Resurrecting costimulation for CD8+ memory T cells. Issue 7 (July 2016) - van der Heide, Verena; Homann, Dirk
Abstract : Rapid recall responses by memory CD8 + T cells are a critical component of adaptive immunity. The role of CD28 signaling in this process remains ill‐defined. This Commentary discusses an article in this issue that uses a strategy for timed CD28 ablation in an infectious disease model, to evaluate this question. Abstract : Rapid activation and proliferative expansion of specific CD8 + memory T (CD8 + TM ) cells upon antigen re‐encounter is a critical component of the adaptive immune response that confers enhanced immune protection. In this context, however, the requirements for costimulation in general, and CD28 signaling in particular, remain incompletely defined. In the current issue of the European Journal of Immunology, Fröhlich et al . [Eur. J. Immunol. 2016. 46: 1644‐1655] provide definitive evidence that optimal elaboration of CD8 + TM ‐cell recall responses is indeed contingent on CD28 expressed by these cells. Here, we discuss the "CD28 costimulation paradigm" in its historical context and highlight some of the unresolved complexities pertaining to CD28‐dependent interactions that shape CD8 + T‐cell phenotypes, functionalities, and recall reactivity.